Nanofibers as new-generation materials: From spinning and nano-spinning fabrication techniques to emerging applications - Barhoum, Ahmed; Pal, Kaushik; Rahier, Hubert; Uludag, Hasan; Kim, Ick Soo; Bechelany, Mikhael (Applied materials today, 2019)
[Display omitted] •Nanofibers have their unique properties among other nanomaterials.•This review summarizes the history and development of nanofibers.•It shows their fabrication techniques (using spinning and non-spinning approaches).•It demonstrates their emerging applications in large areas: energy, environment and health.•It highlights the research needed in nanofiber to broaden their industrial applications. Nanofiber unique characteristics and potential applications offer innovative strategies and opportunities for sustainable energy production, and for creative solutions to biomedical, healthcare, and environmental problems. This review summarizes the history and development of nanofiber technology, their unique properties, fabrication techniques (using spinning and non-spinning approaches), and emerging applications in energy harvesting and storage, environmental protection and improvement, and biomedical technology and healthcare. Nanofibers are currently used as electrode and membrane materials for batteries, supercapacitors, fuel cells, and solar cells. Nanofiber membranes are also successfully used for ultra-high air filtration, wastewater treatment, water purification, and blood purification at low pressure. This review will describe the different types of nanostructured fibers (e.g., solid, mesoporous, hollow, core–shell nanofibers) fabricated from natural and synthetic polymers, metal and metal oxides, carbon-based, inorganic–organic hybrid nanofibers and their potential applications. Moreover, it will highlight the current and future research needs in nanofiber-based materials to improve and broaden their applications and commercialization.